Clinical Efficacy of Modified Small Incision Thyroidectomy and Analysis of Influencing Factors of Postoperative Hypocalcemia - Zhou, Jian; Ju, Hongqing; Ma, Hongyan; Diao, Qixian (Frontiers in Surgery, 2022)
Objective Analyze the clinical effect of modified small incision thyroidectomy and evaluate the influencing factors of hypocalcemia (EH) in patients after operation. Methods A total of 220 patients with thyroid cancer in our hospital from October 2019 to October 2021 were selected. The patients were randomly divided into a control group and an observation group, with 110 patients in each group. The control group were treated with traditional thyroidectomy, while the observation group were treated with modified small incision surgery. The perioperative indicators of the two groups were compared. The thyroid hormone indexes of the two groups were meansured before operation and 7 days after operation, and the incidence of complications was compared between the two groups. Serum calcium was detected 7 days after operation in both groups. According to the level of blood calcium, patients were divided into EH group and normal group. The data of two groups were compared, and the related factors affecting the occurrence of EH after operation were analyzed. Results The operation time, incision length and intraoperative bleeding volume of patients in the observation group were significantly lower than those of patients in the control group (p < 0.05). There was no significant difference in drainage time and postoperative drainage volume between the two groups (p > 0.05). The postoperative PTH level of patients in the observation group was significantly higher than that in the control group (p < 0.05), but there was no significant difference in FT3, FT4 and TSH levels (p > 0.05). The incidence of postoperative complications in the observation group (11.82%) was significantly lower than that in the control group (34.55%). Logistic regression analysis showed that bilateral lymph node dissection, parathyroidectomy and decreased PTH were the independent risk factors for EH in our patient after operation (p < 0.05). Conclusion The modified small incision operation can effectively reduce the occurrence of surgical trauma and related complications. Bilateral lymph node dissection, parathyroidectomy and PTH decrease are the risk factors for postoperative EH in patients with thyroid cancer. Taking corresponding measures to improve the metabolic function of patients during perioperative period will help to reduce the incidence of postoperative EH in patients with thyroid cancer.